Constructing Social Identity through Language: The English Influence in Production of MSMES - Fauzi, Deri Fikri; Haryani, Heni (International Journal of English and Applied Linguistics (IJEAL), 2024)
This study explores the significant role of English language usage in the production practices of Micro, Small, and Medium Enterprises (MSMES) in Indonesia, particularly focusing on how this linguistic choice reflects social identity within a globalized context. By examining prevalent English terms in product naming—such as "Ready Stock," "Fresh Milk," and "Mango Iced Tea"—the research reveals a deliberate strategy among MSMES producers to position their offerings as modern and appealing to contemporary consumers, especially younger demographics. Interviews with MSMES stakeholders indicate a strong belief that incorporating English enhances product appeal and improves production quantity, underscoring the language's perceived association with quality and sophistication. This dynamic aligns with sociolinguistic theories regarding language as a marker of social identity, where familiarity with English signifies higher social status and aspirational lifestyles. The findings illustrate how MSMES navigates cultural negotiation, blending local heritage with global trends to construct a distinct identity that resonates with both local and international markets. Ultimately, this study highlights the interplay between language, culture, and identity, demonstrating how English usage serves not only as a marketing tool but also as a mechanism for fostering innovation and cultural exchange within Indonesia's culinary landscape. By situating their products within a global narrative, MSMES producers affirm their roles as adaptive and forward-thinking members of an increasingly interconnected world.